Transformational Leadership and Organizational Justice Effect on Organizational Citizenship Behavior Through Organizational Commitment of Employees in the Industry XYZ - Nina Florentina Raisa; Rojuaniah Rojuaniah (Forum Kerjasama Pendidikan Tinggi, 2023)
In the automotive accessories in XYZ industry, quality employees are essential for organizational success. This makes Organizational Citizenship Behavior (OCB) an important aspect of organizational continuity. To determine the relationship between OCB and organizational commitment, analyze the impact of transformational leadership and organizational justice. By using the Structural Equation Model (SEM)-PLS analysis method, this study used a questionnaire with a total sample of 150 employees selected through purposive sampling. The results revealed that 4 out of 5 hypotheses had a positive effect on organizational commitment and OCB with the highest T-value of 7.599. With the exception of transformational leadership having a positive effect on organizational commitment, the hypothesis data is not supported.